Cerita rakyat Jawa Bayu Wibisana, Nanik Herawati ; editor, Nunung Yuli Eti ; ilustrator, Jumadi, M. Yusuf. - BAYU WIBISANA; Nanik Herawati; Nunung Yuli Eti; Jumadi; M. Yusuf (Intan Pariwara, 2010)
iv, 68 hlm. ilus. 21 cm (3 eks.)